AKT Inhibitor SC66 Inhibits Proliferation and Induces Apoptosis in Human Glioblastoma Through Down-Regulating AKT/β-Catenin Pathway - Gao, Lun; Liu, Junhui; Xu, Pengfei; Deng, Gang; Liu, Baohui; Yuan, Fanen; Tan, Yinqiu; Sun, Qian; Xu, Yang; Zhang, Huikai; Qi, Yangzhi; Han, Shoumeng; et al. (Frontiers in Pharmacology, 2020)
Glioblastoma multiforme (GBM) is the most common intracranial malignancy in adults with the highest degree of malignancy and mortality. Due to its nature of diffuse invasiveness and high migration, GBM lacks an effective treatment strategy and is associated with poor prognosis. SC66 is a novel AKT inhibitor that has been reported to exert antiproliferative activity in many types of cancer cells. However, it remains unclear whether SC66 has antitumor effects in GBM. In this study, we found SC66 obviously suppressed U87 and U251 cell proliferation and EMT- mediated cell migration and invasion. Moreover, SC66 induced GBM cells apoptosis and arrested cell cycle in G0/G1 phase. Furthermore, SC66 also downregulated AKT signaling pathway in a concentration dependent manner. We also found the level of β-catenin nuclear translocation was prominently downregulated after SC66 treatment. Meanwhile, TCF/LEF luciferase report assay indicated that the activity of TCF/LEF was remarkably suppressed. Elevating β-catenin activity by using IM12 rescued SC66 inhibition‐mediated GBM cell proliferation and metastasis. In addition, SC66 showed significantly suppressed the tumorigenicity compared to the control group in the xenograft mouse model. In conclusion, our study demonstrated that SC66 exerts prominently antitumor efficiency in GBM cells in vivo and vitro by downregulated AKT/β-catenin pathway.